THE ROLE OF VOCATIONAL HIGHER EDUCATIONS PERSONNEL IN PREPARING PROFESSIONAL - Telly F.S. Tangkere, Henny N. Tambingon (Program Studi Pendidikan Teknologi Informasi dan Komunikasi, Universitas Negeri Manado, 2022)
Improving the quality of vocational education plays a very important role in the development of education in Indonesia. This effort was made because universities as educational institutions in the vocational field produce educators (teachers) and also professional workers. Universities in the field of vocational education must be able to face challenges in the world of work, especially in the world of business and industry. Educators in higher education must also have competence as lecturers who have professionalism in teaching. If the lecturer is professional, then he can teach well in accordance with the field of study that is his expertise. Vocational education in the vocational field in preparing a skilled and educated workforce must also pay attention to the quality of teaching staff, curriculum, facilities, and infrastructure, and other facilities that support the learning process in the field of vocational education. By fulfilling this, students can be prepared as professional workers according to their field of study.